The Time-Saving Bias in a Firm - Zíka, Vojtěch; Dušek, Libor; Miklánek, Tomáš; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2015)
The time-saving bias is a cognitive error which systematically influences human perception of relationship between speed and time. As a consequence they overestimate time gained/lost when accelerating/decelerating from higher speed and underestimate time gained/lost when accelerating/decelerating from lower speed. This bias is most salient in the context of a car driving where such a misperception might lead to an excessively high travelling speed. Apart from the impact on the driving safety, unduly high speed have negative effect also on the fuel economy. An undue fuel consumption can be an issue not only for firms, but also for the environment. This work tested a formerly proposed de-biasing measure, a paceometer, in a field experiment with the intention to find out if this kind of intervention can alter drivers' behaviour in order to reduce speeding and thus increase the driving safety and decrease the fuel consumption. To test also the strength of the measure the experiment was done within a middle size company where employees did not bear driving costs. Results based on 1 year fuel consumption data of 45 participants showed no particular effect of the measure on the average fuel consumption. A reason for this finding can be an existence of a principal/agent problem which considerably affects incentives of drivers.
Vedoucí práce: Libor Dušek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: hospodářská politika [obor dipl. práce]; diplomové práce; master's theses